2020
DOI: 10.3390/biology9050101
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Porcine Follicular Fluid Proteomes of Small and Large Ovarian Follicles

Abstract: Ovarian follicular fluid is widely used for in vitro oocyte maturation, but its in-depth characterization to extract full beneficial effects remains unclear. Here, we performed both shotgun (nanoscale liquid chromatography coupled to tandem mass spectrometry or nanoLC-MS/MS) and gel-based (two dimension-differential in-gel electrophoresis or 2D-DIGE) proteomics, followed by functional bioinformatics to compare the proteomes of follicular fluids collected from small (<4 mm) and large (>6–12 mm) follicles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Studies in bovine model have shown that vitronectin in FF contributes to follicle development [ 26 ]. Additionally, vitronectin promotes sperm-oocyte linking and fertilization [ [27] , [28] , [29] ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in bovine model have shown that vitronectin in FF contributes to follicle development [ 26 ]. Additionally, vitronectin promotes sperm-oocyte linking and fertilization [ [27] , [28] , [29] ].…”
Section: Discussionmentioning
confidence: 99%
“…As expected, increases in glutathione and ROS follow the development of the oocytes, their metabolic rate and demand for more energy. In addition, pathways involved in cellular components such as gap junctions indicate great activity and high responsiveness of cells to stimulus‐response, cell adhesion, differentiation and proliferation (Paes et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pathways involved in cellular components such as gap junctions indicate great activity and high responsiveness of cells to stimulus-response, cell adhesion, differentiation and proliferation (Paes et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, oocytes matured in a medium containing PFF showed enhanced embryonic development [ 34 ]. Generally, PFF is aspirated from the antral follicles, and the composition of PFF differs depending on the size of follicles [ 35 ]. A previous study reported that cumulus cell viability, monospermic fertilization of IVF embryos, and subsequent embryonic developmental competence are reduced in oocytes matured in medium containing PFF derived from small antral follicles (3–4 mm in diameter), compared to oocytes matured in medium containing larger (5–6 mm in diameter) follicle-derived PFF [ 36 ].…”
Section: Discussionmentioning
confidence: 99%